(untitled) (World Science, 2020)
The main factors affecting the formation of recreational and health complexes in Ukraine are identified in the article. Importance of unique recreational potential of Ukraine and establishment of recreational and health rehabilitation facilities is proved. The research indicates that modern recreational and health complex is a synergy of natural potential, the latest rehabilitation and medical technologies, professionalism of employees and uniqueness of architectural solutions. The significance of architectural solutions goes beyond aesthetic perception and comfort. Architecture of these objects significantly affects the person’s physical health due to elaborate location of the building, its area-based planning and design of facades and interiors. Proposals for optimal placement of recreational and health complexes and their volume-spatial and functional planning solutions can be developed only as a result of analysis of economic, social, climatic and urban factors.